The Used of Inductive Approach to Improve Students Speaking in Professional Context at the Second Semester Students of STKIP PGRI Lubuklinggau - Ayu Oktaviani; Yulfi Yulfi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The objective of the research was to find out how students speaking in professional context at the 2nd semester of STKIP PGRI Lubuklinggau can be improved through inductive approach. The researcher used Action Research or classroom action research. The research conducted at STKIP PGRI Lubuk Linggau academic year 2014/2015. The research conducted to the students who took speaking class (Speaking for Professional context). The class consists of 34 students. The procedures of the actions were four steps as follows: (1) planning, (2) implementing, (3) observing and (4) reflecting. The findings of the strategy implementation were analyzed from the research instruments used, observation checklists, field notes, speaking test and Interview. There were thirty four (34) students as the samples of class room action research. Based on the product of test, they were 30 of 34 students (88.24 percent) successfully passed the final of speaking test. Based on the interview of 34 students in second semester only 6 students who were still not confidence in speaking and there were 28 students or (82.35 percent) who did not feel easily embarrassed when they spoke in the class especially in formal class. Based on the data above, this classroom action research succeeds to improve students skill in speaking for professional context. It means that, inductive approach that has 6 steps, 13 meeting, and 7 topics was success. Keyword: Speaking, Professional Context, Inductive, Approach